The intensity of a resistance exercise session can be quantified by the work rate of exercise. - Brendan R Scott; Kieran J Marston; Shaun Y M Teo; Mitchell R L Forrest; Andrew Jonson; Thomas P Walden; Brook Galna; Jeremiah J Peiffer (PLoS ONE, 2023)
Purpose Athletes regularly perform resistance training, yet it is unknown how best to monitor its intensity. This study compared different resistance exercise intensity metrics to determine their sensitivity to manipulating work rate (via altering inter-set rest and load). Methods Following baseline testing for 10- and 3-repetition maximum (RM; squat and bench press), fourteen trained participants completed four volume-matched protocols in a randomised order: 3x10 with 85% 10RM, 60 s rest (3x1060s); 3x10 with 85% 10RM, 180 s (3x10180s); 8x3 with 85% 3RM, 120 s (8x3120s); 8x3 with 85% 3RM, 300 s (8x3300s). Internal intensity was quantified via rate of oxygen consumption ([Formula: see text]), heart rate, blood lactate concentration, and rating of perceived exertion (RPE). External intensity was assessed via previously developed "Training-Intensity" (TI) and "Intensity-Index" (II) metrics, and from exercise work rate (expressed as kg∙min-1 and joules∙min-1). Results Internal intensity and work-rate metrics were highest for 3x1060s, followed by 3x10180s, 8x3120s and 8x3300s (p≤0.027). TI and II were higher for 8x3 than 3x10 protocols (p<0.001), but not different within these configurations. Internal intensity measures were more strongly correlated with work rate (r = 0.37-0.96) than TI and II (r = -0.42-0.33) metrics. Conclusions Work rate corroborated objective internal intensity metrics during resistance exercise, with the highest work rate session (3x1060s) also eliciting greater RPE scores than other protocols. In contrast, the TI and II did not agree with other intensity measures, likely because they do not consider rest periods. Practitioners can plan for the physiological and perceptual demands of resistance training by estimating work rate.